2014
DOI: 10.1016/j.lrr.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Human endogenous retrovirus np9 gene is over expressed in chronic lymphocytic leukemia patients

Abstract: The human genome contains a large number of endogenous retroviruses (HERVs). Their reactivation has frequently been observed in patients with cancer. Considering their role in the carcinogenesis process, we aimed to study the possible relationship between HERVs gene expression and Chronic Lymphocytic Leukemia (CLL). We focused on two viral genes gag and np9, the latter presumably an oncogene. We found that the transcriptional activity of HERV-K np9 gene was greater in CLL patients than in healthy donors. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 10 publications
(14 reference statements)
0
30
0
1
Order By: Relevance
“…HERV-K is thought to be transcriptionally silent in normal cells, and becomes active after malignant transformation (8,11), except in the case of brain tumors (12). Increased expression of HERV-K has been detected in human cancers (8,1321), and transcripts of HERVs have been detected by many independent investigators in various types of cancer that include breast cancer (8,22,23), ovarian cancer (24, 25), lymphoma (26,27), melanoma (11,2832), germ line tumors (3335), and prostate cancer (5, 36). Our laboratory showed that the HERV-K family is active and overexpressed in breast cancer (2,23,3740): HERV-K expression was detected in 45% to 93% of primary breast tumors (N=479), and a higher rate of lymph node metastasis was associated with HERV-K-positive compared with HERV-K-negative tumors.…”
Section: Introductionmentioning
confidence: 99%
“…HERV-K is thought to be transcriptionally silent in normal cells, and becomes active after malignant transformation (8,11), except in the case of brain tumors (12). Increased expression of HERV-K has been detected in human cancers (8,1321), and transcripts of HERVs have been detected by many independent investigators in various types of cancer that include breast cancer (8,22,23), ovarian cancer (24, 25), lymphoma (26,27), melanoma (11,2832), germ line tumors (3335), and prostate cancer (5, 36). Our laboratory showed that the HERV-K family is active and overexpressed in breast cancer (2,23,3740): HERV-K expression was detected in 45% to 93% of primary breast tumors (N=479), and a higher rate of lymph node metastasis was associated with HERV-K-positive compared with HERV-K-negative tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic lymphocytic leukemia (CLL) cells demonstrate increased transcription of auxillary HERV-K/HML-2 (ERVK) gene Np9, which was previously published as possible oncogene [211]. Indeed, silencing of Np9 inhibits the growth of myeloid and lymphoblastic leukemic cells, whereas its overexpression promotes the growth in vitro and in vivo.…”
Section: Cancermentioning
confidence: 99%
“…It would also be interesting to further explore the scope of np9 and rec upregulation in even more cancers. Although we used RNA-seq files from 15 different types of cancer, there are more cancer types reported in the literature to overexpress HERVs: colorectal cancer [37] , chronic lymphocytic leukaemia (CLL) [38] , and Burkitt's lymphoma [39] . Further research could also be performed to characterise the broad network that indicates how Np9 and Rec proteins interact with effectors in the MAPK/Akt/NOTCH signalling cascade that ultimately leads to cell survival and proliferation, specific to the cancers they are upregulated in.…”
Section: Discussionmentioning
confidence: 99%